Taxonomy of the business models of successful pharmaceutical products in Iran with a focus on competitive drugs in the growth phase - Ali Asgar Halvaei; Mahdi Ebrahimi (کاوش‌های مدیریت بازرگانی, 2022)
Introduction: Today, one of the best tools available for value chain engineering is applying the practical lessons of business models. By analyzing a business model, the processes of development, presentation and receipt of value by a company can be improved. Although many companies operating in different industries of the country have increasingly turned to the analysis of their business models, the issue is moving forward at a lower speed in the pharmaceutical industry. Numerous new business models have been developed or renovated in today’s changing business environment. The development and renovation of new business models are not a matter of choice but a necessity in order to survive in an environment whose rules of the game are constantly changing. In such a situation, the greatest challenge posed to organizations is developing a framework through which an accurate understanding of the dimensions and components of their business models can be achieved and a point of reference can be offered to compare their business models with those of the competing companies to enable innovation and outperformance. The main focus of this study is to find a practical framework for pharmaceutical companies so as to identify and compare the key features of their business models with those of active competitors, hence to understand the strengths and positive qualities of other models and overcoming their weaknesses.In this study, the latest scientific findings about the business models of pharmaceutical companies are presented, and the common types of these business models are identified using taxonomy (experimental typology) to achieve a more comprehensive and accurate view of the dynamics of this business model in companies.Methodology: The statistical population of this study included all the Iranian companies producing human drugs that have had a competitive product in the growth stage. The study was conducted in two phases, content analysis and quantitative phase. Initially, semi-structured interviews during the content analysis phase revealed a comprehensive framework for the dimensions and components of the business model of Iranian pharmaceutical companies, and then, through quantitative surveys and in-person questionnaires, the business model of each pharmaceutical company was identified. The sampling method in the qualitative part of the research was judged after 19 theoretical saturation interviews, and the quantitative research became available. By using the PASS software, an optimal sample of 40 companies was adopted. In this study, the empirical classification (taxonomy) approach, rather than the ideal classification (typology), was used to identify various business models. In clustering methods, since the data are classified irrespective of any presupposition or predetermined framework, the fuzzy c-means (FCM) clustering algorithm serves as the most appropriate tool to attain the typological objective of this study.Results and Discussion: Finally, by fuzzy clustering with the MATLAB software, four distinct variants of the business model were identified for the pharmaceutical companies, each having significant differences in the key features of the business models with the other types. These four types included Diverse Effectiveness, Concentrated Effectiveness, Diverse Effectiveness, Concentrated Effectiveness. The identified types have specific similarities and differences in each business model dimension and component which can be concisely compared as follows based on their key features including concentration on quality rather than on efficiency, extent of relationships in various areas such as sales, marketing, and raw material supply.Conclusion: The competitive pharmaceutical products in Iran can be categorized in four distinct types in terms of the characteristics of their business model. These models have different characteristics in terms of the amount of value proposition, the processes of shaping the value architecture, the mechanisms for interaction with different groups of customers and value acquisition methods. Finally, these types of business models were named based on their proprietary features as: diversified effective, focused effective, diversified efficient and focused efficient. The first business model type was labeled “diversified effective” as it is greatly focused on quality and extensive relationships with various stakeholders of the value chain. Companies such as CinnaGen, Exir, SobhanDarou, DarouPakhsh, Osvah, and Samisaz had the greatest degree of membership in this business model type. The second type was labeled “diversified efficient” as it is highly concentrated on cost control and extensive relationship maintenance with the value chain stakeholders. Companies such as ParsDarou, TehranShimi, AlborzDarou, TehranDarou, and Actoverco had the greatest degree of membership in this business model type. The third type was labeled “focused efficient” and included such pharmaceutical companies as Hakim, CaspianTamin, Sepidaj, Loghman, and Jalinous which had the greatest degree of membership in this business model type. Finally, the fourth type was labeled “focused effective” and involved companies such as Shafa, Ronak, DinehIran, and Modava with the greatest degree of membership therein.